2000
DOI: 10.1002/1097-0215(20001001)88:1<1::aid-ijc1>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diet on serum albumin and hemoglobin adducts of 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP) in humans

Abstract: 2‐Amino‐1‐methyl‐6‐phenylimidazo[4,5‐b]pyridine (PhIP) is the most abundant heterocyclic amine formed in meat and fish during cooking and can be used as a model compound for this class of chemicals possibly involved in human carcinogenesis. Knowing the exposure to heterocyclic amines is important for establishing their role in human diseases. Serum albumin (SA) and globin (Gb) adducts were first tested as biomarkers of exposure to PhIP in male Fischer 344 rats given oral doses of 0.1, 0.5, 1 and 10 mg/kg. Bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 30 publications
(62 reference statements)
2
67
0
Order By: Relevance
“…These three compounds have been detected in beef, lamb, pork, chicken and fish, especially when chargrilled, fried or roasted (Gooderham et al 2001;Turesky 2007). PhIP and MeIQx are potent mutagens in bacterial and mammalian cell genotoxicity assays and induce colon tumors in rats; less genotoxicity data are available for DiMeIQx Magagnotti et al 2000;Nishikawa et al 2005;Turteltaub et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…These three compounds have been detected in beef, lamb, pork, chicken and fish, especially when chargrilled, fried or roasted (Gooderham et al 2001;Turesky 2007). PhIP and MeIQx are potent mutagens in bacterial and mammalian cell genotoxicity assays and induce colon tumors in rats; less genotoxicity data are available for DiMeIQx Magagnotti et al 2000;Nishikawa et al 2005;Turteltaub et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…It is generally thought that total HCA adduction to albumin in vivo is substantially greater than to haemoglobin (Turesky and Le Marchand, 2011); however, one study (Magagnotti et al, 2000) demonstrated acid labile PhIP-Hb adducts to be only two-fold lower than albumin adducts. Our protein adducts prepared in vitro contain HCAs at concentrations approximately four orders of magnitude greater than PhIPprotein adducts described in vivo in the few studies which have quantified albumin or haemoglobin adducts in people consuming conventional diets (Magagnotti et al, 2000) or dietary-relevant doses of radiolabelled PhIP (Dingley et al, 1999). This high level of adduction is similar to that reported for in vitro adduction of reactive metabolites of PhIP to albumin (Peng and Turesky, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…Residues of HCAs adducted to blood proteins have been postulated for some years as potential medium-term biomarkers of carcinogenic HCA exposure (Peng and Turesky, 2011;Magagnotti et al, 2000;Dingley et al, 1999). However, the viability of quantifying HCAs following their release from such adducts in vivo has not been proven in people consuming diets encompassing the normal range of HCA intakes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations